Feeling Included and Valued: How Perceived Respect Affects Positive Team Identity and Willingness to Invest in the Team. (17th October 2011) - Ellemers, Naomi; Sleebos, Ed; Stam, Daan; de, Dick
<x xml:space="preserve">Abstract</x> Previous research has documented that intra‐group respect fosters individual engagement with work teams or organizations. The authors extend this work by empirically distinguishing between perceived inclusion of the self in the team and perceived value of the self for the team as separate psychological consequences of respect. Based on a social identity analysis, it is predicted that perceived inclusion facilitates the development of a positive team identity (how the individual feels about the team), while perceived value elicits the willingness to invest in the team (what the individual is willing to do for the team). Support for these predictions is obtained with structural equation modelling among two independent samples of professional soldiers working in military teams (ntotal = 495). Reports of individual team members about positive team identity and willingness to invest in the team correlated with supervisor ratings of the team's action readiness.